Помогите пожалуйста очень срочно надо. Упростите выражения : 1 ) а ( а + 2b ) - ( b + a )^2= 2 ) ( m + 4 )^2 - ( m - 3 ) ( m + 3 )= 3 ) 3 ( b - 1 )^2 + 8b= 4) (n+5)^2 - n(n -7)= . 5) 2c(8c -3)-(4c+ 1)^2 =. 6)(6 - n)(n+6) +(n...

Помогите пожалуйста очень срочно надо. Упростите выражения : 1 ) а ( а + 2b ) - ( b + a )^2= 2 ) ( m + 4 )^2 - ( m - 3 ) ( m + 3 )= 3 ) 3 ( b - 1 )^2 + 8b= 4) (n+5)^2 - n(n -7)= . 5) 2c(8c -3)-(4c+ 1)^2 =. 6)(6 - n)(n+6) +(n-4)^2=. 7) (2+a)(2-a)(4-a^2) - a^4=. 8) (m+n)(m-n)(m^2 -n^2)+2m^2 n^2 =. 9)(a+3)(a-3)(a-3)(a+3)+18a^2=. 10) (x+2)^2 * (x - 2)^2 - x^4+16 =
Гость
Ответ(ы) на вопрос:
Гость
1) а ( а + 2b ) - ( b + a )^2= a^2+2ab-b^2-2ab-a^2=-b^2 2) ( m + 4 )^2 - ( m - 3 ) ( m + 3 )=m^2+8m+16-m^2-3m+3m+9=8m+25=0 m=25/8=4.1
Не нашли ответ?
Ответить на вопрос
Похожие вопросы